A study on factors influencing on employee retention in Company A / Muhammad Fakhrul Zaman Hamil - Hamil, Muhammad Fakhrul Zaman (Faculty of Business and Management, 2018)
Employee retention is a common issues that happen in organization especially in private sector. It is not easy to retain an employees for a long period in organization. This is because employee can simply find a new job if they do not have more interest to remain in the organization. The purpose of this study is to identify the factors that influence on employee retention at Company A. In this study, researcher has listed three independent variables such as reward and recognition, supportive work environment, and continuous learning and employee retention. Moreover, the study was conducted by using systematic sampling method and Questionnaire to gain data from respondent. The questionnaire was distributed to the 36 of respondent in Company A. Furthermore, the researcher used Statistical Package for Social Science (SPSS) version 22 to get a result for findings and analysis of study. So, the finding of study found that reward and recognition, supportive work environment, and continuous learning had significant, moderate and strong relationship with employee retention. Nevertheless, the findings proved that independent variables continuous learning has the most factor that influence on employee retention.